SIKAP DAN PERSEPSI MASYARAKAT DESA MANGUNANG SEBERANG TERHADAP KEGIATAN PENDAMPINGAN TIM PASCASARJANA ULM TENTANG TEKNOLOGI INOVASI GULA AREN DAN PENGEMASANNYA - Rosidah Muis Radam; Dina Naemah; Arfa Agustina Rezekiah; Yuniarti Yuniarti; Muthia Elma; Yusuf Aziz (Lambung Mangkurat University-Indonesia, 2020)
he purpose of this research is to measure the level of perception and attitude towards the mentoring post-graduate team. The method used in data collection is a live interview using structured questionnaires and direct observations to measure the skills of respondents. Purpossive Random samplingtechniqueto 20 respondents was applied. The parameters are observed counseling/socialization activities, the training of sugar-making innovations, the training of palm sugar products and the training of liquid sugar products and the packaging of brown sugar products. The results showed that public attitudes and perception of socialization activities showed 100% understand the content of material, demonstration processing of palm sugar Products innovations 60% understand and will try to cultivate, 40% understand just do not try to cultivate; Demonstration brown sugarprocessing 85% understand and will try to do, and 15% just look at the process and would try for livelihood needs, processing liquid sugar 50% who enthusiastically understand and 50% less understanding, packaging the product modeled 75% understand and interested, 25% do not understand and have no desire to make packaging.